(3GdYOGdI GdJUGdMjI ai GdehGO GdLfGFjI (B: s (3OQGSI ebGQfI (B/ s - (3CMeO YHOGddg CMeO GdNhdis; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3YQVfG ai gPg GdOQGSI dehVhY GdYOGdI GdJUGdMjI ai GdehGO GdLfGFjI(B: (3Pdc GdehVhY GdPi jTZd HGd abgGA GdbGfhf GdLfGFi; HGYJHGQg CMO eMGhQ Md CReI GdYOGdI GdLfGFjI(B: (3ai Xd aTd Mdhd GdYOGdI GdLfGFjI GdJbdjOjI ai UhQJgG GdYbGHjI(B. (3h bO JecffG ef Gdhbha Ydi LhgQ GdYOGdI GdJUGdMjI GdbGFe Ydi CacGQ JJeKd ai(B: (3LHQ GdVQQ GdeJQJH Ydi GdLQjeI(B: (3h RjGOI GdOhQ GdGjLGHi ddeLfi Ydjg ai JMOjO eUjQ GdOYhi GdLfGFjI(B: (3h EYGOI JCgjd GdLGfi dEOeGLg ai GdeLJeY eQI CNQi(B. (3h ERGA eG JbOe GQJCjfG Cf fbSe HMKfG gPG Edi HGHjf(B: (3h GSJgOafG ef gPG GdJbSje Cf fVY fXQjI YGeI ddYOGdI GdJUGdMjI(B: (3JTed GdCWQ GdadSajI(B: (3h cPG GdLhGfH GdYedjI GdJWHjbjI dJdc GdfXQjI(B: (3h Pdc cdg ai EWGQ OQGSI ebGQfI eY GdfXe GdbGfhfjI GdeNJdaI ShGA cGfJ dGJjfjI Ch CfLdhCeQjcjI ddhbha Ydi eXGgQ GdYOGdI GdJUGdMjI ai eNJda Ohd GdYGde(B. (3aai GdHGH GdChd HMKfG ai eSCdI GdYOGdI GdJUGdMjI ai Xd GdfXe GdELQGFjI ddOYhi GdLfGFjI(B: (3acGf gPG GdHGH HeKGHI EWGQ fXQi ddHMK(B: (3GfWdbfG ajg HOGjI ef eaghe GdYOGdI GdJUGdMjI(B: (3h fTCJgG(B: (3h JWhQgG Edi Cf CUHMJ oJPcQ UQGMI ai GdbhGfjf GdLfGFjI GdELQGFi cbGfhf GdELQGAGJ GdLfGFjI GdaQfSi(B. (3h ai GdHGH GdKGfi JWQbfG dGSJbQGA BdjGJ h JWHjbGJ GdYOGdI GdJUGdMjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2020s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B302323s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdLQGFe GdJUGdMjIs; (3GdbGfhf GdLfGFis; (3GdehGO GdLfGFjIs; (3GdYOGdI GdLfGFjIs; (3GdLQjeI GdOhdjIs; (3GdhSGWI GdLfGFjIs; (3GdJaGhV Ydi GdGYJQGas; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs